Silent sinus syndrome in children. (July 2020) - Freiser, Monika E.; McCoy, Jennifer; Shaffer, Amber D.; Stapleton, Amanda L.
Abstract: Introduction: Silent sinus syndrome (SSS) is defined as a progressive enophthalmos and hypoglobus associated with maxillary sinus atelectasis. There is extremely limited literature describing SSS in children. The goals of this study are to characterize SSS in children through an IRB approval retrospective chart review of cases identified through a large health system-wide imaging database and to compare the presentation and outcomes of patients who underwent surgery versus those who were observed. Methods: A radiology database of over 26 million reports from 2003 to 2017 was searched to identify children aged 1–18 years diagnosed with maxillary sinus hypoplasia or SSS on CT scan. Chart review was performed on the identified children including clinical presentation, eye symptoms, surgical treatment, and outcome. Results: Eighty-three children were identified to have maxillary sinus hypoplasia. Eighty-one patients had maxillary sinus opacification and 57 patients had hypoglobus or enophthalmos characteristic of SSS. Thirty-two patients (47%) were seen by a specialist and 19 had surgery. The majority of patients (55%) had headache as their presenting symptom. There were no statistically significant differences in the clinical presentation between those who received surgery and those who were observed clinically. Conclusions: Silent sinus syndrome can present at any age. The majority of cases of maxillary sinus hypoplasia will have the orbital floor changes characteristic of SSS. Headaches are a common presenting symptom. Close follow up of pediatric patients is advised and early intervention may be favorable to prevent long term orbital changes and complications. Highlights: Silent sinus syndrome can be present in children as young as 3 years of age. Age of presentation of silent sinus syndrome does not correlate with the severity of disease. A majority of cases of maxillary sinus hypoplasia in children will have orbital floor changes characteristic of SSS